The status quo and future prospects of digital twins for healthcare - Teng Li; Yi Shen; Yuxiang Li; Yongbo Zhang; Song Wu (EngMedicine)
Digital twin technology plays a pivotal role in driving the digital transformation of healthcare services. This review provides a comprehensive overview of the applications of digital twins in the healthcare sector. We elucidate the concept and classification of digital twins for healthcare and provide a detailed account of their current applications in clinical diagnosis, treatment, and hospital operational management. Taking the cardiac digital twin as an example, this review showcases the typical use of digital twins in clinical practice and scientific research. Additionally, the challenges faced by digital twin technology in data collection, model construction, ethics, and regulations were analyzed. Finally, the broad prospects of digital twins in promoting precision and personalization in healthcare are envisioned.